1998
DOI: 10.1292/jvms.60.853
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Antibody to Neospora caninum in Japanese Dogs.

Abstract: ABSTRACT. Prevalence of antibody to Neospora caninum (NC) in Japanese dogs were examined. The antibody was positive in 15 of 48 dogs (31.3%) reared in the dairy farms that had case of the abortions due to NC infection or had the cattle seropositive to NC, whereas the prevalence was 7.1% (14 of 198 dogs) among the dogs kept in urban areas. In one dog breeder, all 17 Shetland sheepdogs older than 7 months were seropositive, and one pup was diagnosed as neosporosis 2 months before the first serological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
26
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 7 publications
13
26
0
10
Order By: Relevance
“…Globally, there were no seroprevalence differences in relation with age, sex or general clinical aspect. The absence of difference between males and females is in agreement with several studies [10,19,38]. However, a higher frequency in females was previously reported [6].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Globally, there were no seroprevalence differences in relation with age, sex or general clinical aspect. The absence of difference between males and females is in agreement with several studies [10,19,38]. However, a higher frequency in females was previously reported [6].…”
Section: Discussionsupporting
confidence: 93%
“…The lowest seroprevalences were found in groups 2 and 3 (police squad and kennels) whereas the highest seroprevalences were found in stray and farm dogs. This is in agreement with several studies indicating that seroprevalences are higher in farm dogs or pounds dogs than in urban dogs [9,10,[22][23][24][25][26][27][28][29][30][31][32]. In breeder (urban) dogs the seroprevalence was 12.08% which is close to the data available in similar urban dog populations [31,41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presence of T. gondii has been reported in domestic cats in Japan (Hagiwara, 1977;Fujinami et al, 1983) and recent studies have shown positive rates ranging between 5.4% (Maruyama et al, 2003) and 6.0% (Nogami et al, 1998). Sawada et al (1998) reported that 15 of 48 dogs (31.3%) raised on dairy farms having cases of cattle abortion due N. caninum infection were positive for antibody to N. caninum, whereas the occurrence of antibodies in dogs from an urban area was 7.1% (14 of 198 dogs). If wildlife populations continue to grow, and urbanization continues to expand, this will increase the chance of contact between domestic animals and wildlife.…”
mentioning
confidence: 97%